Role Stress, Turnover Intentions Auditor, Kepemimpinan Hindu dan Kompensasi - Syanuri, Ni Nyoman Kosi; Sari, Maria Mediatrix Ratna (E-Jurnal Akuntansi, 2022)
The purpose of the study was to determine the effect of role conflict, role ambiguity and role overload on turnover intentions of auditors with Hindu leadership and compensation as moderating variables. The study was conducted at 14 Public Accounting Firms in Bali. The number of samples obtained as many as 77 respondents using purposive sampling technique. The hypothesis was tested using Smart Partial Least Square (Smart PLS). Based on the research results, it is known that role conflict and role ambiguity have a positive effect on turnover intentions, but role overload has no significant effect on turnover intentions. Based on the research that has been done, it is also known that Hindu leadership can weaken the influence of role conflict and role overload on turnover intentions but cannot moderate the effect of role ambiguity on turnover intentions. Compensation can weaken the effect of role conflict and role overload on turnover intentions but cannot moderate the effect of role ambiguity on turnover intentions. Keywords: Role Conflicts; Role Ambiguity; Role Overload; Turnover Intention; Hindu leadership; Compensation.